Atšķirība starp augsta un zema līmeņa valodām - Kiyasov, Valikhon (Latvijas Universitāte, 2024)
: Comparison of Low-Level vs. High-Level Programming Languages This article will explain a comparative study of the features, uses, and effectiveness of low-level and high-level programming languages. Low-level languages, such as Assembly and C++ , offer a small level of abstraction from hardware and allow the programmer to have very fine control over the system resources. Such a feature is needed for developing embedded systems and drivers. High-level languages, such as Python and Java offer significant levels of hardware abstraction. Emphasis is put on use-by facilities and quick development; therefore, these languages are also suited to be used to develop application software, web development, and wherever speed of development is important. This paper intends first and foremost to establish what kinds of trade-offs these languages make between control and convenience and then to evaluate the appropriateness of the trade-offs for different kinds of software development. Current research gives the proof that low-level languages do excel in performance and in the optimization of resources, while high-level languages bring about increased productivity and maintainability because of the less complex syntax and strong libraries. The practical part of this investigation elaborates on dedicated case studies in which each language category can be better utilized, reviews code samples, and also shows performance benchmarks. The results are such that the popularity of high-level languages, while less effective than low-level, is derived from their versatility and ability to manage large and complex projects efficiently. More research should be conducted on the emerging languages and frameworks that permit better confluence of low-level control and high-level efficiency. Keywords: High-level languages, Low-level languages, Programming languages, Syntax, Abstraction, Performance, Algorithm
Difference between high and low level languages
Keywords: Datorzinātne; High-level languages; Low-level languages; Programming languages; ion; Performance